Perfil de abdome agudo cirúrgico em pacientes com HIV/AIDS em um hospital de referência no estado do Pará - PASCOAL, Giselly de Fátima Mendes (Universidade Federal do Pará, 2015)
The Acquired Immunodeficiency Syndrome (AIDS) is a disease of the human immune system caused by the human immunodeficiency virus (HIV). HIV attacks human cells responsible for defending the body from diseases, and the CD4 + T cells most affected. Abdominal pain in immunocompromised patients with difficult management evolves diagnosis is mandatory for the surgeon to be familiar with the various differential diagnoses and secondary complications of AIDS. This study aimed to describe the clinical and epidemiological aspects of AIDS patients who developed acute abdomen and received surgical treatment from January 2001 to January 2011 at the University Hospital João de Barros Barreto. It was an observational, retrospective, case-control, where the case group consisted of patients with HIV / AIDS who developed acute abdomen and the control group of patients who have progressed to acute abdomen, but no immunosuppressive condition associated. Patients were predominantly male ratio 4.5 men for every woman in the group with AIDS, but with similar proportion in controls. Most patients (87%) of the control group had a laboratory abnormality, unlike the group with HIV / AIDS, where 38.5% of patients had normal results. Anemia was present in 75% of patients with HIV / AIDS and leukocytosis in 80% of the control group. The most frequent cause of acute abdomen in the population with HIV / AIDS was intestinal perforation (82.1%), while the control group was intestinal obstruction (39.1%). Only the clinical picture of abdominal defense and decreased bowel sounds showed statistically significant (p <0.01). Radiological changes occurred in 87.2% of patients with HIV / AIDS showed distension and 65.2% of control patients showed air-fluid levels. The main surgery performed in the group HIV / AIDS was a bowel resection with primary reconstruction of traffic (65.5%). Surgical complications were more frequent in the group with HIV / AIDS (87.2% with wound infection) and the predominant cause of death in both groups was sepsis from abdominal focus (81% in cases and 87.5% controls ), including in patients ostomates. The probability of death in patients with HIV / AIDS was higher by about 2-fold compared to controls. The length of hospital stay and postoperative time to death was lower in AIDS patients compared to controls. Being fundamental to the study to improve the management and survival of patients with HIV / AIDS.